Assessment of the accuracy of the Greulich and Pyle hand-wrist atlas for age estimation in a contemporary Australian population. Issue 4 (4th July 2018) - Maggio, Ariane; Flavel, Ambika; Hart, Rob; Franklin, Daniel
Abstract: Age estimation of living individuals is topical, and is particularly important globally, owing to increasing migration of undocumented individuals. Radiographic skeletal analysis of hand-wrist skeletal development is often used to infer chronological age based on direct comparison to standards such as the Greulich and Pyle atlas. However, this atlas has been criticised for being applied to foreign populations without due consideration of accuracy. The aims of the current study are to assess the precision and accuracy of the atlas in a contemporary Western Australian population and to develop population specific standards based on the latter system. The study sample comprised 360 individuals (equal sexes) and aged from birth to 25 years; a hold-out group comprising a further 50 individuals was used for model validation. Age estimation was performed through the visual comparison of the study radiographs against the atlas standards; statistical analyses were performed to assess the relationship between estimated skeletal and actual age. Prediction models were formulated; mean SEE values were ±0.005–0.90 (male) and ±0.25–0.421 years (female). Comparisons with prior research demonstrates the importance of contemporary population standards. The models presented here have forensic utility in a Western Australia jurisdiction, albeit the level of accuracy achieved is not suitable for the specific determination of legal majority.